Gendered anthropomorphism in human–robot interaction: the role of robot gender in human motivation in task contexts - Zhu, Yi; Su, Ling; Zheng, Lijing (Frontiers in psychology, 2025)
This study investigates how gendered anthropomorphism in robots influences human motivation to undertake challenging tasks within human–robot collaborative settings. Through two experiments—a survey-based experiment (Study 1, N  = 169) and a behavioral experiment (Study 2, N  = 130), we observed how a collocated female- versus male-gendered robot assistant affects participants’ willingness to accept a challenging task. Results revealed that interactions with female-gendered robots elicited significantly greater willingness to undertake a challenging task compared to male-gendered counterparts. This finding advances our understanding of human motivation in modern workplace environments that integrate robotic technologies, and underscores the critical role of gender cues in robot design, particularly in collaborative settings where task engagement and performance are prioritized.